Creep Modeling in a Composite Rotating Disc with Thickness Variation in Presence of Residual Stress - Vandana Gupta; S. B. Singh (International Journal of Mathematics and Mathematical Sciences)
Steady-state creep response in a rotating disc made of Al-SiC (particle) composite having linearly varying thickness has been carried out using isotropic/anisotropic Hoffman yield criterion and results are compared with those using von Mises yield criterion/Hill's criterion ignoring difference in yield stresses. The steady-state creep behavior has been described by Sherby's creep law. The material parameters characterizing difference in yield stresses have been used from the available experimental results in literature. Stress and strain rate distributions developed due to rotation have been calculated. It is concluded that the stress and strain distributions got affected from the thermal residual stress in an isotropic/anisotropic rotating disc, although the effect of residual stress on creep behavior in an anisotropic rotating disc is observed to be lower than those observed in an isotropic disc. Thus, the presence of residual stress in composite rotating disc with varying thickness needs attention for designing a disc.